A Genealogy of the Socialist Self? The Approach to the History of Psy-Sciences in Europe after 1945 in Contemporary Historiography and Sociology - Střelec, Jakub (Dějiny – teorie – kritika, 2020)
This article explores scholarly literature dealing with the history of psy-sciences in Europe after 1945. It is interested, primarily, in historical and sociological research based on Michel Foucault’s genealogy of the self. The main aim of this article is to provide insights into current discussions in the history of psy-sciences in Europe after 1945, and to outline possible research themes in the history of psy-sciences in Czechoslovakia between 1948 and 1989. In order to do so, this article is structured as follows: the first part introduces research dealing with the relation between psy-sciences and neoliberalism in Western Europe; the second part analyses research focusing on the shaping of the socialist self in the Eastern Bloc; the third part introduces new studies in the history of psy-sciences that use the methodology of the material turn in their analysis. In conclusion, this article argues that the history of psy-sciences can contribute to the research about communist Czechoslovakia with several new research topics.